EFFECT OF SERVOMYCES® ADDITIVES ON DIFFERENT GENERATIONS OF YEAST DURING BEER FERMENTATION - Obradović, Valentina; Škrabal, Svjetlana; Marčetić, Helena; Laljek, Draženka; Ergović Ravančić, Maja (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Beer is produced from malt, hops, water and brewer's yeast through the process of alcoholic fermentation. In the production of beer, selected strains of brewer's yeast of the Saccharomyces uvarum species are used for the so-called lager beer (bottom-fermented beer), while to produce ale beer (top-fermented beer) the species Saccharomyces cerevisiae is used, and different hybrids of these yeasts can also be used. During fermentation, the yeast ferments the sugars from the wort into alcohol and CO2. The products of its metabolism are also by-products such as vicinal diketones, which significantly affect the aroma and quality of beer. Special attention is paid to the yeast propagation process. Servomyces® is one of the additives produced as a supplement for the needs of the brewing industry. The aim of this work was to determine the effect on 1st, 2nd and 3rd generation yeasts, and to determine possible differences between fermented beer to which the additive Servomyces® was added at the end of the brewing process, compared to fermented beer that was produced by the standard process. For this purpose, the apparent extract and concentration of vicinal diketones were monitored during the fermentation process, and at the end of fermentation, the degree of overcooking and the percentage of dead yeast cells were measured. The reduction of vicinal diketones was monitored 6-9 days after the end of fermentation. It was found that the reduction of vicinal diketones is the same or slightly faster with the addition of Servomyces®, with a slightly lower concentration at the end of fermentation, and that the proportion of the apparent extract remained unchanged. The number of dead yeast cells was lower in yeast supplemented with Servomyces®